Exosomal formulation of anthocyanidins against multiple cancer types. (1st May 2017) - Munagala, Radha; Aqil, Farrukh; Jeyabalan, Jeyaprakash; Agrawal, Ashish K.; Mudd, Ashley M.; Kyakulaga, Al Hassan; Singh, Inder P.; Vadhanam, Manicka V.; Gupta, Ramesh C.
Abstract: Over the last two decades, berries and berry bioactives, particularly anthocyanins and their aglycones anthocyanidins (Anthos) have demonstrated excellent anti-oxidant, anti-proliferative, apoptotic and anti-inflammatory properties. However, their physicochemical and pharmacokinetic limitations such as, low permeability, and poor oral bioavailability are considered as unfavorable properties for development as drugs. Therefore there is a need to develop systems for efficient systemic delivery and robust bioavailability. In this study we prepared nano-formulation of bilberry-derived Anthos using exosomes harvested from raw bovine milk. Exosomal formulation of Anthos enhanced antiproliferative and anti-inflammatory effects compared with the free Anthos against various cancer cells in vitro . Our data also showed significantly enhanced therapeutic response of exosomal-Anthos formulation compared with the free Anthos against lung cancer tumor xenograft in nude mice. The Anthos showed no signs of gross or systemic toxicity in wild-type mice. Thus, exosomes provide an effective alternative for oral delivery of Anthos that is efficacious, cost-effective, and safe, and this regimen can be developed as a non-toxic, widely applicable therapeutic agent. Highlights: Milk exosomes can serve as a vehicle to berry bioactive, anthocyanidins (Anthos). Anthocyanidins were stable in exosomal formulation for weeks. Exosomes alone exhibited anti-proliferative and anti-inflammatory effects. Exosomal formulation of Anthos provide enhanced activity compared with free Anthos. Oral delivery of ExoAnthos caused significant inhibition of lung tumor xenografts.